Bentuk ketidakadilan gender dan perlawanan tokoh Kinanti dalam novel Layangan Putus (kajian feminisme eksistensialisme Simone de Behaviour) - Meivitasari, Yessy; Widyatwati, Ken (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
The purpose of this research is to analyze gender injustice and the form of resistance of Kinanti's character in the novel “Layangan Putus” based on Simone de Behaviour's Existentialism Feminism theory. The approach used in this research is the feminism approach. The auxiliary theory used is Simone de Behaviour's existentialism theory. The research method used is descriptive qualitative. In this research, the type of literature research is used. The data analysis technique in this research focuses on Kinanti's character. The results showed forms of gender injustice and discriminatory behavior towards Kinanti's character. Furthermore, there is resistance from Kinanti's character as a form of existence. The change of thought in Kinanti's character at the beginning of the story, which was deepening religious knowledge to obey the head of the family, became Kinanti, who is currently supporting herself with the title she has. The resistance carried out by the character Kinanti is a form of proof of the injustice she felt during her time as Aris's wife.